Ginsenoside Rb 1: A novel therapeutic agent in Staphylococcusaureus-induced Acute Lung Injury with special reference to Oxidative stress and Apoptosis. (June 2020) - Shaukat, Aftab; Yang, Chao; Yang, Yaping; Guo, Ying-fang; Jiang, Kangfeng; Guo, Shuai; liu, Junfeng; Zhang, Tao; Zhao, Gan; Ma, Xiaofei; Wu, Zhiming; Zhou, Qingqing; et al.
Abstract: Acute lung injury (ALI) is considered as an uncontrolled inflammatory response that can leads to acute respiratory distress syndrome (ARDS), which limits the therapeutic strategies. Ginsenosides Rb1 (Rb1), an active ingredient obtained from Panax ginseng, possesses a broad range of pharmacological and medicinal properties, comprising the anti-inflammatory, anti-oxidant, and anti-tumor activities. Therefore, the purpose of the present study was to investigate the protective effects of Rb1 against S. aureus-induced (ALI) through regulation of Nuclear factor erythroid 2-related factor 2 (Nrf2) and mitochondrial-mediated apoptotic pathways in mice ( in-vivo ), and RAW264.7 cells ( in-vitro ). For that purpose, forty Kunming mice were randomly assigned into four treatment groups; (1) Control group (phosphate buffer saline (PBS); (2) S. aureus group; (3) S . aureus + Rb1 (20 mg/kg) group; and (4) Rb1 (20 mg/kg) group. The 20 μg/mL dose of Rb1 was used in RAW264.7 cells. In the present study, we found that Rb1 treatment reduced ALI-induced oxidative stress via suppressing the accumulation of malondialdehyde (MDA) and myeloperoxidase (MPO) and increase the antioxidant enzyme activities of superoxidase dismutase 1 (SOD1), Catalase (CAT), and glutathione peroxidase 1 (Gpx1). Similarly, Rb1 markedly increased messenger RNA (mRNA) expression of antioxidant genes (SOD1, CAT and Gpx1) in comparison with ALI group. The histopathological results showed that Rb1 treatment ameliorated ALI-induced hemorrhages, hyperemia, perivascular edema and neutrophilic infiltration in the lungs of mice. Furthermore, Rb1 enhanced the antioxidant defense system through activating the Nrf2 signaling pathway. Our findings showed that Rb1 treated group significantly up-regulated mRNA and protein expression of Nrf2 and its downstream associated genes down-regulated by ALI in vivo and in vitro . Moreover, ALI significantly increased the both mRNA and protein expression of mitochondrial-apoptosis-related genes (Bax, caspase-3, caspase-9, cytochrome c and p53), while decreased the Bcl-2. In addition, Rb1 therapy significantly reversed the mRNA and protein expression of these mitochondrial-apoptosis-related genes, as compared to the ALI group in vivo and in vitro . Taken together, Rb1 alleviates ALI-induced oxidative injury and apoptosis by modulating the Nrf2 and mitochondrial signaling pathways in the lungs of mice. Graphical abstract: Image 1 Highlights: Rb1, is obtained from Panax ginseng, having anti-oxidant and anti-apoptotic properties. Rb1, save lung from S. aureus -induced oxidative damage via Nrf2 pathway. Rb1, alleviates ALI-induced apoptosis by modulating mitochondrial signaling.